Efficacy of CG 3 R 6 TAT Nanoparticles Self-Assembled from a Novel Antimicrobial Peptide for theTreatment of Candida albicans Meningitis in Rabbits - Xu, K.; Wang, H.; Liu, Lihong; Xu, W.; Sheng, J.; Fan, W.; Yang, Y.; Li, L. (Karger, 2011)
Background: Candidal meningitis is a common clinical manifestation of invasive candidiasis in neonates. The aim of this study was to evaluate the in vivo antifungal efficacy of CG3R6TAT nanoparticles, novel core-shell structures self-assembled from cationic antimicrobial peptides, in a rabbit model of candidal meningitis. Methods: In vitro activity of CG3R6TAT nanoparticles against Candida albicans was assessed by determining the minimum inhibitory concentration and kill-time curves. In vivo, intravenous treatment with CG3R6TAT nanoparticles (n = 6; 0.25 mg/kg/day) or fluconazole (n = 6; 100 mg/kg/day) began 3 days after infection and continued for 11 consecutive days; the efficacy was assessed following 11 days of treatment by yeast counting in cerebrospinal fluid (CSF), the leukocyte concentrations in CSF and the histopathology of brain parenchyma. Results: At a concentration three times higher than the minimum inhibitory concentration (8.1 µmol/l), the nanoparticles completely sterilized C. albicans after 5 h of incubation. In addition, there was a significant reduction in fungal counts and leukocyte concentrations in the CSF from rabbits treated with CG3R6TAT nanoparticles or fluconazole versus those from untreated control rabbits (p < 0.05, ANCOVA). The median number of days of treatment required to sterilize CSF cultures was 8.5 days for CG3R6TAT nanoparticle therapy (p = 0.022, vs. control) and 9.7 days for fluconazole therapy (p > 0.05, vs. control). The histopathologic severity of rabbits was significantly attenuated after CG3R6TAT treatment (p = 0.001, vs. control). Conclusion: This study suggests that CG3R6TAT nanoparticles may be a promising therapeutic agent for candidal meningitis.